The Construction of The Myth of Honor in The Film Theeb: A Roland Barthes Semiotic Analysis - Meisya Putri Thahirah; Nurlinah Nurlinah; Asep Supianudin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
his study examines the construction of the myth of Bedouin honor in the film Theeb (2014) directed by Naji Abu Nowar using Roland Barthes' semiotic framework. Theeb was selected because it strongly represents Bedouin cultural values, particularly the concept of honor (sharaf), as the central theme of its narrative, yet has never been specifically studied through Barthesian semiotics with a focus on myth construction. This study aims to identify how the myth of Bedouin honor is constructed in the film and to reveal the naturalization mechanisms that make honor appear as a natural and self-evident cultural identity. A qualitative descriptive method was employed, using close viewing technique on 35 data points comprising key dialogues and scenes, analyzed at three levels of meaning: denotation, connotation, and myth. The findings reveal that the myth of Bedouin honor in Theeb is constructed through four mutually reinforcing values: hospitality toward guests (diyafa), loyalty and brotherhood (wafa'), courage (shaja'a), and family reputation (sharaf al-nasab). This construction naturalizes honor through three main mechanisms: the ritualization of everyday actions, heroification without dramatization, and the essentialism of inheritance. Together, these mechanisms conceal the historical and ideological dimensions of honor, presenting it as an innate characteristic of Bedouin male identity rather than a cultural construction shaped by specific historical conditions. This study contributes to the field of Arab film semiotics and enriches understanding of how film not only represents culture but also actively constructs and naturalizes particular ideologies that shape perceptions of cultural identity.